2019
DOI: 10.1177/2050313x19877274
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous sarcoidosis in a melanoma scar: A case report

Abstract: Sarcoidosis is an inflammatory multisystemic disease of unknown etiology with multiple presentations of cutaneous lesions. It characteristically infiltrates scars due to several kind of trauma such as surgery, tattoo and even herpes zoster. We present a case of a 65-year-old woman with progressive distal paresthesia and motor weakness. She was referred to our dermatology clinic for a new violaceous nodular plaque within an old melanoma scar on the posterior neck. On positron emission tomography–computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Demirkök et al described scar sarcoidosis of a thyroidectomy scar 17 years after the procedure 7 . Scar sarcoidosis was also reported within the site of a previous melanoma scar 4 years after the procedure, as described by Fournier et al 8 . Our patient developed cutaneous manifestations 5 years after initial diagnosis without recurrence of systemic involvement to date.…”
Section: Discussionmentioning
confidence: 73%
“…Demirkök et al described scar sarcoidosis of a thyroidectomy scar 17 years after the procedure 7 . Scar sarcoidosis was also reported within the site of a previous melanoma scar 4 years after the procedure, as described by Fournier et al 8 . Our patient developed cutaneous manifestations 5 years after initial diagnosis without recurrence of systemic involvement to date.…”
Section: Discussionmentioning
confidence: 73%
“…Several studies identified inorganic agents in tissue of sarcoidosis patients. Based on the observation that sarcoidosis can be seen in tattooed areas and scars [13,14], Colboc et al studied biopsies of cutaneous sarcoidosis patients for the presence of inorganic deposits in granulomatous areas [15]. Using polarized light, birefringent material was observed in granulomas of 5 out of 14 sarcoidosis patients, whereas birefringent material or inorganic deposits were not observed in any of the included controls.…”
Section: Histopathological Exposure Assessmentmentioning
confidence: 99%